2015
DOI: 10.14302/issn.2372-6601.jhor-15-666
|View full text |Cite
|
Sign up to set email alerts
|

The Silver, Cobalt, Chromium, Iron, Mercury, Rubidium, Antimony, Selenium, And Zinc Contents In Human Bone Affected By chondrosarcoma

Abstract: Objectives: To clarify the role of trace elements in the etiology and the pathogenesis of the chondrosarcoma, a non-destructive neutron activation analysis with high resolution spectrometry of long-lived radionuclides were performed. Methodology:The silver (Ag), cobalt (Co), chromium (Cr), iron (Fe), mercury (Hg), rubidium (Rb), antimony (Sb), selenium (Se), and zinc (Zn) mass fractions and Co/Zn, Cr/Zn, Fe/Zn, Hg/Zn, Sb/Zn, Co/Rb, Cr/Rb, Fe/ Rb, Hg/Rb, Sb/Rb, and Se/Rb mass fraction ratios were estimated in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A high Se level was reported in malignant tumors of the ovary [58], lung [59], prostate [60][61][62][63][64][65][66][67][68], breast [69,70], gastro intestinal tract [71], and also in cancers of the stomach [72] and thyroid [73]. Moreover, in our previous study elevated levels of Se were found in such malignant tumors of bone as osteogenic sarcoma [74], chondrosarcoma [75], and malignant giant cell tumor of bone [76]. The role played by Se in those tumors remains unknown, but in general it is accepted that certain proteins containing Se can mediate the protective effects against oxidative stress.…”
Section: Seleniummentioning
confidence: 95%
“…A high Se level was reported in malignant tumors of the ovary [58], lung [59], prostate [60][61][62][63][64][65][66][67][68], breast [69,70], gastro intestinal tract [71], and also in cancers of the stomach [72] and thyroid [73]. Moreover, in our previous study elevated levels of Se were found in such malignant tumors of bone as osteogenic sarcoma [74], chondrosarcoma [75], and malignant giant cell tumor of bone [76]. The role played by Se in those tumors remains unknown, but in general it is accepted that certain proteins containing Se can mediate the protective effects against oxidative stress.…”
Section: Seleniummentioning
confidence: 95%
“…A high Se level was reported in malignant tumors of the ovary [59], lung [60], prostate [61][62][63][64][65][66][67][68][69], breast [70,71], gastro intestinal tract [72], and also in cancers of the stomach [73] and thyroid [74]. Moreover, in our previous study elevated levels of Se were found in such malignant tumors of bone as Ewing's sarcoma [75], chondrosarcoma [76], and malignant giant cell tumor of bone [77]. The role played by Se in those tumors remains unknown, but in general it is accepted that certain proteins containing Se can mediate the protective effects against oxidative stress.…”
Section: Seleniummentioning
confidence: 97%
“…water volume, including the blood volumes, in tissues [79]. Cancerous tissues are predominantly highly vascularized lesions [80][81][82][83][84][85]. Thus, it is possible to speculate that thyroid malignant tumors are characterized by an increase of the mean value of the Cl mass fraction because the level of tumor vascularization is higher than that in normal thyroid tissue.…”
Section: Twenty Chemical Element Contents In Normal and Cancerous Thymentioning
confidence: 99%